Integration of Global SDGs Issues in Science Material: Curriculum Review - Idris, Nahri (Scientica Education Journal, 2025)
This study aims to examine the extent to which global issues in the Sustainable Development Goals (SDGs) are integrated into Natural Science (IPA) subject matter in the 2013 Curriculum and the Independent Curriculum in Indonesia. The method used is descriptive qualitative with a document analysis approach to national curriculum documents and science textbooks for elementary and secondary education. The results show that the integration of SDGs in science material has begun, especially in themes such as the environment, energy, and climate change. However, this integration is not evenly distributed and remains implicit. The Independent Curriculum provides greater space for the development of contextual learning based on global issues, while textbooks and learning guides still need to be adjusted to support integration with the SDGs. Strengthening of learning policies and guidelines is needed so that teachers can develop science learning with a sustainable perspective in a more systematic and comprehensive manner